Analysis of Factors Influencing Hospitalization Costs for Patients with Lung Cancer Surgery Based on the BP Neural Network. (June 2014) - Huang, Lijuan; Liang, Xuezhu; Zha, Junjing
Abstract Objective. To analyze the factors influencing the hospitalization costs of patients undergoing lung cancer surgery, based on the back-propagation (BP) neural network model, and to provide support for controlling the costs effectively. Method. To collect the hospitalization data of 168 cases of patients with lung cancer surgery from January 2010 to December 2013, and then analyze the influencing factors of the different classified hospitalization costs based on the BP neural network. Results. The expenses on drugs and consumables comprise the largest proportion of the total cost of hospitalization, at 34.35% and 23.24% respectively. The length of hospital stay is the most important factor in the hospital costs. The patients with longer hospital stay have higher costs and the difference is significant (P < 0.05). Conclusion. The hospitals should control their charges on drugs and consumables reasonably and reduce the length of hospital stay effectively, so as to reduce the economic burden on lung cancer patients to the greatest extent possible.